Terapia ocupacional na atenção básica em saúde no município de São Carlos: um enfoque nas pessoas com deficiência e nas pessoas com sofrimento mental - Bassi, Bianca Gonçalves de Carrasco (2012)
In years 2000, stimulated for the Strategy Health of the Family and for the governmental investments in its had emerged ascending reflections on the Primary Health Care. In this context, the objective work to know the politics, the actions and the nets in health destined to the people with deficiency and people with mental suffering, in the city São Carlos, SP, are problem of the study in the scope of the Primary Health Care. As methodology resource it was used documentary analysis, specifically reports of the municipal conferences of health and the municipal plan of health, and interview half structuralized with civic, professional managers of health, such as: occupational therapists, physiotherapists and nutritionist, beyond users of the services, people with deficiency or people with mental suffering. One searched to portray the local context, weaveeing connections with the context of the Brazilian public politics, in the attempt to foment dialogues with realities of other cities of average Brazilian transport. 24 interviews, being 06 with managers, 12 with health professionals had been carried through (05 physiotherapists, 06 occupational therapists, 01 nutritionist), 06 with users of the services (03 people with deficiency and 03 people with mental suffering). The results show to a change in construction in the paradigm of the attention in health of the city, directed to the model of monitoring in health with qualification proposals of the Primary Health Care , centered in the Strategy Health of the Family, aiming at to the formation and joint of a Net School of Cares to the Health. However, the inexistence of politics and specific municipal lines of direction of care for the people with deficiency and the people with mental suffering, delicate the care in health destined for such populations. The Primary Health Care in São Carlos intention to be directed for the integral care, however, this speech, and the approach in the actions of promotion and prevention of health, determines not the priorities of actions come back toward specific and complex demands as those of the people with deficiency and the people with mental suffering. Specifically with regard to the occupational therapists, the data present that the initial actions of these professionals, just-inserted in the Primary Health Care, are come back in its majority toward the mental health, however also notice action next to other populations. These professionals act in the with Primary Health Care proposals of promotion of health, shelter and action of whitewashing. This professional in the becomes essential, that, commits itself to the problems and the concrete necessities of the population of each territory and to the social paper of its performance. He concludes yourself that in the scene placed for the Politics of Basic Attention in Brazil, its institutionalization convokes the construction of new plans of care in health and constants theoretical reflections to base the actions techniques, specifically come back toward not traditionally received populations in this scope.